The Dignity of Labor in Islam: Ethical Principles and Contemporary Relevance - Mahmudulhassan, M; Abuzar, Muhammad; Khondoker, Saif Uddin Ahmed; Khanom , Jobeda (Suhuf: International Journal of Islamic Studies, 2025)
This study investigates the concept of labour dignity in Islamic ethical teachings, focusing on how foundational Islamic texts conceptualize the rights and responsibilities of workers and employers. While numerous studies address Islamic economic principles or general labour rights, few have examined labour dignity specifically through an ethical lens that integrates both classical sources and contemporary applications. This research aims to fill that gap by systematically analyzing how Islamic principles—drawn from the Qur'an, Hadith, and Islamic jurisprudence—can inform modern work ethics and labour practices. The study adopts a qualitative content analysis approach, using targeted keywords such as Islamic labour ethics, the dignity of work in Islam, and social justice in Islamic thought to review relevant primary and secondary literature. The findings indicate that Islam upholds labour dignity through core values such as fair compensation, mutual respect, social responsibility, and anti-exploitation norms. Workers are regarded not merely as economic agents but as participants in spiritual and communal growth, while employers are ethically obligated to ensure just treatment. The study contributes to Islamic labour ethics scholarship by bridging religious doctrines with contemporary socio-economic discourse, offering theoretical insight and practical recommendations for promoting equity and justice in diverse labour environments.